WP15 ConCorD state-of-the-art report (container corrosion under disposal conditions) - Muñoz, Andrés G.; Abdelouas, Abdesselam; Alonso, Ursula; Fernández, Ana María; Bernier-Latmani, Rizlan; Cherkouk, Andrea; Gaggiano, Roberto; Hesketh, James; Smart, Nick; Padovani, Cristiano; Mijnendonckx, Kristel; Montoya, Vanessa; et al. (Frontiers in Nuclear Engineering, 2024)
A sealed container for the geological disposal of spent nuclear fuel and vitrified high-level waste is the only component of the deep geological repository that provides complete containment of radionuclides. As such, attention is focused on its lifetime. The lifetime of the container is influenced by materials degradation processes during disposal and is typically of the order of several millennia and, for some container materials, up to one million years. Designing, manufacturing, and predicting the performance of containers over such long periods requires an in-depth understanding of their materials properties, fabrication processes, and degradation mechanisms. Scientific and technological progress can improve both the performance of containers as well as the robustness of lifetime predictions. For many national radioactive waste disposal programs, optimization of these aspects is of primary importance. In this paper, the state of the art of complex coupled degradation processes, as well as the optimization potential of novel container materials is presented. Furthermore, the existing tools allowing the prediction of long-term barrier integrity are discussed.